149: Temperament Is Associated with Free Play in Young Children. Issue 6 (1st June 2014) - Sharp, JR; Maguire, J; Carsley, S; Abdullah, K; Lebovic, G; Chen, Y; Parkin, PC; Birken, CS
Abstract: BACKGROUND: There is emerging evidence that child temperament is associated with sedentary behaviours and obesity in young children, but physical activity (PA) has not been evaluated. Parent-reported outdoor free play correlates with directly measured PA in young children. OBJECTIVES: The primary objective is to determine if Negative Affectivity, a construct of child temperament, is associated with outdoor free play in young children. Secondary objectives are to determine if the constructs of Surgency and Effortful Control are each associated with outdoor free play. DESIGN/METHODS: Subjects were children <6 years old (n=3784) recruited through TARGet Kids! primary care-based research network. Child temperament was measured by the Children's Behaviour Questionnaire. The primary exposure was Negative Affectivity. The outcome was parent-reported daily outdoor free play (minutes). A linear regression model was performed, adjusting for covariates of age, sex, ethnicity, income, maternal employment, daycare use, presence of siblings, and presence of family rules. Age, sex and family rules were identified a priori as potential interactions, and stratified analysis was planned. Analysis was repeated with Effortful Control and Surgency as exposures. RESULTS: On average, children participated in outdoor free play for 58 min/day. Outdoor free play was significantly associated with Negative Affectivity (P<0.01) and Surgency (P=0.01), but not Effortful Control (P=0.23). Multivariate analysis including interactions revealed that sex had a significant moderating effect; adjusting for covariates, boys, but not girls, with higher Negative Affectivity had reduced outdoor free play. For boys at the lowest and highest quartile of outdoor free play time, with each one-point increase in Negative Affectivity, free play was reduced by 3.5 min/day (95% CI 1.8 to 5.2 min/day), and 6.2 min/day (95% CI 3.1 to 9.4 min/day), respectively. For Surgency, age had a significant moderating effect. Adjusting for covariates, children older than two years with higher Surgency had increased outdoor free play; for the lowest and highest quartile of free play, with each 1-point increase in Surgency, free play increased by 3.1 min/day (95% CI 0.9 to 5.3 min/day), and 4.5 min/day (95% CI 1.3 to 7.8 min/day), respectively. There was no association found for children less than two years old. CONCLUSIONS: Negative Affectivity and Surgency are temperaments shown to be associated with outdoor free play in young children. This information may help in the development of effective interventions to promote PA in this age group.